2013
DOI: 10.18633/bt.v15i3.153
|View full text |Cite
|
Sign up to set email alerts
|

EXTRACCIÓN DE COMPUESTOS FENÓLICOS DE LA CÁSCARA DE LIMA (Citrus limetta Risso) Y DETERMINACIÓN DE SU ACTIVIDAD ANTIOXIDANTE

Abstract: Recibido: 28 de noviembre de 2012 Aceptado: 17 de enero de 2013 RESUMEN Los desechos que se tienen de la obtención de jugos son principalmente cáscara y bagazo, sin embargo son una buena fuente de compuestos fenólicos, mayoritariamente de flavonoides. El objetivo de este trabajo fue extraer y cuantificar el contenido fenólico de la cáscara de lima, así como su actividad antioxidante. Esto se determinó evaluando el mejor sistema de extracción de compuestos fenólicos y flavonoides, teniendo como variables: tipo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…A total of 8 methanolic plant extracts were tested against 5 clinical bacterial isolates. Methanol was selected as extraction solvent, because it is one of the best solvents used for the extraction of antimicrobial substances [ 29 , 30 ]. Moreover, methanol polarity ensured the extraction of polar and moderately polar active compounds from plants against microorganisms like terpenoids, tannins, flavones, and polyphenols [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8 methanolic plant extracts were tested against 5 clinical bacterial isolates. Methanol was selected as extraction solvent, because it is one of the best solvents used for the extraction of antimicrobial substances [ 29 , 30 ]. Moreover, methanol polarity ensured the extraction of polar and moderately polar active compounds from plants against microorganisms like terpenoids, tannins, flavones, and polyphenols [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, chiltepin pepper showed different antioxidant activity behavior by each of the 3 methods, which can be associated to the different mechanism involved in each method. DPPH is an antioxidant capacity method that measures mainly lipophilic compounds, while the ABTS is associated with the antioxidant activity of hydrophilic compounds in alcoholic extracts (Pérez-Nájera et al, 2013). In addition, both methods base their results on the neutralization of a free radical, which is more representative of the behavior of oxidative stress at biological level.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted in Table 2, in most treatments FRAP values were approximately twice as those obtained through DPPH. Nevertheless, is possible that some antioxidant compounds, such as carotenoids and some sugars can interfere in the measurement of DPPH methodology (Pérez, Lugo, Gutiérrez & Del-Toro, 2013).…”
Section: Discussionmentioning
confidence: 99%